(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The development of modern fields of human activity that require knowledge in the world is determined by the increasing role of computer technologies. Today, the flow of information is increasing significantly, now there is a need to search for new methods of storing, presenting, formalizing and organizing them, as well as automatic processing. Therefore, there is a growing interest in comprehensive knowledge bases that can be used for various practical purposes. In particular, there is a great need for systems based on neural networks that extract any information from the text without the human factor. This article provides suggestions and recommendations for the creation of thesauruses and the linguistic base of adjective vocabulary.